Colour Removal from Textile Dyeing Wastewater Using Different Adsorbents: Adsorbents Study for Textile Effluents - Butt, Muhammad Tahir; Imtiaz, Naz; Ahmed, Sameer; Arif, Farooq; Khan, Shahid Rehman (Biological Sciences - PJSIR, 2010)
The ability of different adsorbents/coagulants, such as liquid and solid polymers, ferric chloride, calcium carbonate and coal ash, was investigated for uptake of (reactive dyes, Red - 120, Yellow - 14 and Blue - 4 from textile dyeing waste. Coal ash was used for the colour removal from the textile dyeing wastewater of reactive dyes. Different adsorbents removed the colour from the effluent in different degrees; in some cases the colour was removed 100%. White polymer was ineffective. Calcium carbonate gave excellent results. Liquid polymers were better effective than the solid ones. Coal ash yielded good results without any further treatment.